JELMAAN REPTILIA DALAM AKAL BUDI MASYARAKAT IBAN: ANALISIS SEMANTIK INKUISITIF (Reflection of Reptiles in Iban Mind: An Inquisitive Semantics Approach) - Rynna Sha’erra, Mindew Douglas; Mary Fatimah, Subet; Muhammad Zaid, Daud (UNISZA, 2023)
Images of reptile animals are often debated in various fields such as science, education and their use in proverbs of Malay idioms and Iban idioms. Observation of the characteristics of animals in these classes makes the Iban community more sensitive toward their surroundings. In the Iban idioms, the images of reptiles used are due to the inherent properties of the animals that are equated or reflected in the nature and actions of men in the past. A total of 15 Iban idioms using images of reptiles were generated from Bup Sempama Iban, a book written by Casper Kayong Umping (2011).. The proverbs data were analyzed using the Semantic Inquisitive Approach by applying the Bridging Cross Reference toward the corpus data. Based on the analysis, the proverbs using the images of reptiles show the traits possessed by humans and they are conveyed by the use of proverbs (Sempama Jaku Iban) with implied meanings and subtle language to keep the recipient's heart or listeners. The merging of data, the applied theory, and the culture applied in this study has successfully explained the implicit meaning behind the Iban idioms and the reflection of the minds of the speakers.